Penyusunan SOP (Standard Operational Procedures) Perpustakaan untuk Meningkatkan Mutu Pelayanan Perpustakaan Perguruan Tinggi - Elva Rahmah (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2012)
The implementation of SOP (Standard Operational Procedures) in university library is needed to improve the service quality. The arrangement of SOP in University library includes four stages. The first is analysis of SOP needs. The beginning step in arranging of SOP is by analyzing SOP that will be created. Furthermore, the SOP that created depends on the ongoing work condition and procedures. The second is the development of SOP. Because of the change of internal and external organization of university library, SOP also has to change. The third is implementation of SOP. In implementing SOP, it is hoped that there is a balance between the availability of SOP, that organizes the operational activity of university library, and the human resources, that have professional behavior in arranging the library. The fourth is observation and evaluation. In order to implement SOP properly, it should be assessed by reviewers. These four steps are done in sequence to produce SOP that is appropriate to field needs for supporting the completeness of integrated quality management in university library. Therefore, the standard service quality of library can be measured by having SOP. Thus, the service quality which is given to visitors can be determined based on SOP. Keywords: library service, service quality, SOP